Incidental finding of a giant intracardiac angioma infiltrating both ventricles in a 35-year-old woman: a case report - Hirschberg, Kristóf; Wiedmann, Felix Tobias; Zitron, Edgar; Fortner, Philipp; Riffel, Johannes; Chorianopoulos, Emmanuel; Gdynia, Georg; Mechtersheimer, Gunhild; Andrassy, Martin; Szabó, Gábor; Arif, Rawa; Katus, Hugo; et al. (Journal of medical case reports, 2016)
Primary cardiac tumors are rare and often asymptomatic or present with unspecific symptoms. Benign cardiac tumors of vascular origin are especially rare, with only few existing data in the literature.